2008
DOI: 10.1111/j.1570-7458.2008.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of integrated pest management on food and horticultural crops in Africa

Abstract: In sustainable agricultural development, integrated pest management (IPM) can play a key role in the reduction of crop losses, thereby increasing productivity while minimizing environmental contamination and health hazards. In recent years, agricultural research and development partners have pioneered outstanding contributions in IPM, notably in varietal resistance against pests, biological control of alien invasive species, substitution of inorganic pesticides with biopesticides, new export market opportuniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Many of our top agricultural pests instead have been created by the use of pesticides that often have a stronger effect on natural antagonists than on the target species, and also because of widespread insecticide resistance (Pimentel et al 1992;Elzen and Hardee 2003;Oerke 2006). This is particularly relevant in developing countries, where agricultural production must be increased to feed the population (Thrupp 2000;Pretty et al 2003;Nwilene et al 2008).…”
Section: Sustainable Insect Control and Food Securitymentioning
confidence: 97%
“…Many of our top agricultural pests instead have been created by the use of pesticides that often have a stronger effect on natural antagonists than on the target species, and also because of widespread insecticide resistance (Pimentel et al 1992;Elzen and Hardee 2003;Oerke 2006). This is particularly relevant in developing countries, where agricultural production must be increased to feed the population (Thrupp 2000;Pretty et al 2003;Nwilene et al 2008).…”
Section: Sustainable Insect Control and Food Securitymentioning
confidence: 97%
“…Research into farmers' perceptions and knowledge around pests and forms of pest control meant to increase crop production (Nwilene, Nwanze, & Youdeowei, 2008) has found that despite the economic, environmental, personal, and social disadvantages of synthetic pesticides (Ahouangninou et al, 2012;Ajayi, Akinnifesi, & Sileshi, 2011;Williamson, Ball, & Pretty, 2008), farmers can often perceive them as the most reliable approach for controlling pests -seeing them as either more effective than alternatives, as the only option available, or simply a last resort, even as they may fail to be adequately effective anyway (Jensen, 2000;Toda & Morishita, 2009). As our current study found, for instance, even when farmers are aware of a more cost-effective and less harmful alternative IPM pesticide, they can still remain reluctant to use it.…”
Section: Introductionmentioning
confidence: 99%
“…Nwilene et al (2008) reviewed the impact of integrated pest management on food and horticultural crops in Africa and described several successes such as biological and varietal approaches to pest management, human capital development and farmer field schools. Despite these successes they conclude, however, that the potential of IPM in Africa is still poorly realised.…”
Section: Integrated Pest Management (Ipm) and Biological Controlmentioning
confidence: 99%